Legal space monitoring: theoretical and legal aspects - Vladimirovich Zhuzhgov, Igor; Aleksandrovich Volkov, Alexander; Mikhailovich Salnyy, Andrey; Borisovna Kulikova, Tatiana; Alexandrovna Ryasnyanskaya, Natalia (Opción, 2019)
The article is concerned with the analytical understanding of the problems related to the sphere of organization and monitoring of the legal space of the Russian Federation with the aim to identify and outline the theoretical and organizational aspects of legal space monitoring. The theoretical characte- ristics of monitoring are given. The features of legal monitoring of social relations are considered and its definition is derived. Bill monitoring is analyzed. The features of law monitoring are explored. The elements of law enforcement monitoring are characterized. The theoretical problems of legal space monitoring are considered. The methods used in legal space monito- ring are analyzed. The legal experience of the subjects participating in legal space monitoring is studied. The scientific novelty is in the scientific defini- tion of the concept of "monitoring", and the identification of monitoring elements as a system. The features of legal monitoring of social relations are considered. Legal space monitoring is studied; the need to include legal monitoring of social relations, bill monitoring, monitoring the law and law enforcement monitoring in the legal space monitoring is justified. The methods used in legal space monitoring and the legal status of the individual subjects of legal space monitoring are covered.